OCT Angiography in angioid streaks without neovascular complications - El Matri, K.; Falfoul, Y.; Hassairi, A.; Chebil, A.; Ammari, M.; El Matri, L. (Acta ophthalmologica (Oxford, England), 2017)
Purpose To describe the features of angioid streaks (AS) without neovascular complications using swept source optical coherence tomography. Methods This is a retrospective observational study. All patients underwent slit‐lamp and fundus examination, fundus photos, swept source optic coherence tomography (SS‐OCT) and OCT angiography (OCT‐A). Comparisons were made between en face OCT and OCT‐A images. Results Seven eyes had AS without neovascular complications, foveola was involved by the streak in 3 eyes of them. In en face OCT, we found hyper‐reflective points in 5 eyes in the deep plexus (DP), and in 2 eyes in the choriocapillaris (CC) giving a shadow in the level of the choriocapillaris in the corresponding OCT‐A. In the outer retina (OR), Streaks were detectable in patients having macular involving AS as hyposignal in the OR and the CC. Also, 5 eyes had CC diffuse rarefaction (CR) that seems more extensive than the masking from the hyper‐reflective material visible in the DP on en face‐OCT. An irregular vascular network (IVN), different from choroidal neovascularisation (CNV), was detected in 3 eyes with AS involving the macula in the level of the OR and CC. This IVN fills spaces between streaks. On structural OCT, it corresponds to flat elevation of the retinal pigmentary epithelium (RPE) with hyper reflective accumulations between the RPE and the Bruch membrane (BM). Conclusions This imaging tool provides new information about AS. We illustrate different findings including hyper reflective deposits, CR and IVN. CR suggests early and severe involvement of all the CC.